2007
DOI: 10.1073/pnas.0605266104
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulocystic kidney disease in mice with a targeted inactivation of Wwtr1

Abstract: Wwtr1 is a widely expressed 14-3-3-binding protein that regulates the activity of several transcription factors involved in development and disease. To elucidate the physiological role of Wwtr1, we generated Wwtr1 ؊/؊ mice by homologous recombination. Surprisingly, although Wwtr1 is known to regulate the activity of Cbfa1, a transcription factor important for bone development, Wwtr1 ؊/؊ mice show only minor skeletal defects. However, Wwtr1 ؊/؊ animals present with renal cysts that lead to end-stage renal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
249
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(270 citation statements)
references
References 42 publications
15
249
2
1
Order By: Relevance
“…TAZ is involved in the development of multiple organs, such as lung, fat, muscle, bone, limb, and heart, as well as many cellular processes, including stem cell differentiation, cell proliferation, and epithelial mesenchymal transition (EMT) 3 (4, 10 -15). Taz knock-out mice develop two severe abnormalities: polycystic kidney disease and emphysema (16,17).…”
mentioning
confidence: 99%
“…TAZ is involved in the development of multiple organs, such as lung, fat, muscle, bone, limb, and heart, as well as many cellular processes, including stem cell differentiation, cell proliferation, and epithelial mesenchymal transition (EMT) 3 (4, 10 -15). Taz knock-out mice develop two severe abnormalities: polycystic kidney disease and emphysema (16,17).…”
mentioning
confidence: 99%
“…The biological functions of the two proteins are not redundant. For example, the Yap knock-out mice are early embryonic lethal while Taz knock-out mice go through normal development but develop cystic renal disease (22,23,35). Furthermore, elevated protein levels of both YAP and TAZ have been found in human cancers, but with clear organ and tissues specificities.…”
Section: Discussionmentioning
confidence: 99%
“…TAZ is involved in the development of multiple organs such as lung, fat, muscle, bone, limb, and heart as well as many cellular processes including stem cell differentiation, cell proliferation, epithelial mesenchymal transition (EMT) 4 (15)(16)(17)(18)(19)(20)(21). Taz knock-out mice develop two severe abnormalities: polycystic kidney disease and emphysema (22,23).…”
mentioning
confidence: 99%
“…Recently, accumulating evidence has shown that effectors of Wnt and Hippo pathways for example, are often shared and crosstalk through multiple mechanisms (for review (110)). Significantly, targeting several effectors of these pathways led to renal cyst formation in the mouse (111)(112)(113)(114)(115)(116)(117). Similarities between dysregulation of polycystin(s) and c-Myc suggest that these proteins are involved in a network or in common signalling pathways essential in renal development and in the ADPKD adult pathologic condition.…”
Section: Orthologous Pkd Mouse Models Co-associate With C-myc Overexpmentioning
confidence: 99%